Improving Student’s Writing Skill Using Recount Text through Online Media Learning - Adinda Nurussadiah; Rizky Mirani Desi Pratama; Dwi Puji Hastuti (Jurnal Sinestesia, 2021)
The research aims to know the student’s ability to write English essays using recount text through online media learning conducted ten students in the tenth class of Rumah Belajar Yayasan Cinta Anak Bangsa (RB-YCAB). The research does online media learning; virtual synchronous learning for material explanation and self-directed asynchronous learning to do the exercises. The research is using qualitative research methods. The data is obtained through several observations and some trials to get results of pre-test and post-test scores. The results show that: (1) Recount text through online media learning helps students’ writing skill can be incredibly effective. (2) Learning recount text through online media learning is coherent and help students in sharpening their memories. (3) Writing ability can improve by the results of the improvement in pre-test and post-test scores. Based on those improvements of a student’s writing ability using recount text through online media learning at Rumah Belajar Yayasan Cinta Anak Bangsa (RB-YACB) is effective.